Creativity in children as function of parent occupation and socio-economic status - Rothe2, J. P. Mankar1, S. U. Ugale1, *S. P. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Present paper deal with the investigation on creativity in children, tested by applying Baquar MahanadiÃ¢â‚¬â„¢s creative thinking test and respectively the parent occupation and socio-economic status, calculating by administrating BharadwajÃ¢â‚¬â„¢s socio-economic status scale. It was hypothesized that Ã¢â‚¬Å“creativity in children as function of parent occupation and socio-economic statusÃ¢â‚¬Â, which was not proved, as the calculated values of r were drawn - 0.05and 0.03 at 5% level of significance, while correlating creativity in children and occupation and socio-economic status of their parents.